2021
DOI: 10.1093/jxb/erab025
|View full text |Cite
|
Sign up to set email alerts
|

Coordination between MIDASIN 1-mediated ribosome biogenesis and auxin modulates plant development

Abstract: Ribosomes are required for plant growth and development, and ribosome-biogenesis-deficiency mutants generally display auxin-related phenotypes. Although the relationship between ribosome dysfunction and auxin has been raised, many aspects of this subject remain to be understood. We previously reported that MIDASIN 1 (MDN1) is an essential pre-60S ribosome biogenesis factor (RBF) in Arabidopsis. In this study, we further characterized the aberrant auxin-related phenotypes of mdn1-1, a weak mutant allele of MDN1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Indole-acetic acid (IAA) and gibberellin have been recognized as the known plant hormones found in plants many decades ago. Some studies have recently demonstrated that various phytohormones such as cytokinins (CTK), abscisic acid (ABA), ethylene, strigolactone, and melatonin are involved in plant growth and development and in responses to stress [ 1 , 2 , 3 , 4 ]. Brassinosteroids (BRs), a new type of plant hormone, have drawn an increased amount of attention.…”
Section: Introductionmentioning
confidence: 99%
“…Indole-acetic acid (IAA) and gibberellin have been recognized as the known plant hormones found in plants many decades ago. Some studies have recently demonstrated that various phytohormones such as cytokinins (CTK), abscisic acid (ABA), ethylene, strigolactone, and melatonin are involved in plant growth and development and in responses to stress [ 1 , 2 , 3 , 4 ]. Brassinosteroids (BRs), a new type of plant hormone, have drawn an increased amount of attention.…”
Section: Introductionmentioning
confidence: 99%
“…). The ARF7 create auxin responsiveness in MND1 and regulate plant development(Li et al 2021). ARF7 regulate the MUS and LBD16 during lateral root development (Xun et al 2020; Singh 2022).…”
mentioning
confidence: 99%
“…Among RBFs, the phenotypic similarity of pointy first leaf extends to mutants lacking in prmt3 (Hang et al, 2014), midasin1 (Li et al, 2021), apum24 (Maekawa et al, 2018), brx1-2 (Weis, Palm, et al, 2015), rh7 (Huang et al, 2016) and irp2 (Palm et al, 2019).…”
Section: Growth Manifestation Due To Mutationmentioning
confidence: 99%
“…Whether such selective mRNA non-translation led to direct perturbation at the proteome level and thus leading to observed growth pleiotropy remains to be established. The leaf patterning defects leading to pointy leaves up on RPs and RBFs mutation have been attributed to impaired auxin signaling in several mutants (Rosado et al, 2010;Abbasi et al, 2010;Rosado et al, 2012;Li et al, 2021). It is likely that similar mechanisms influence the common phenotypic outcomes.…”
Section: Growth Manifestation Due To Mutationmentioning
confidence: 99%